Carbon Stock Of Seagrass In Karang Tirta’s Coastal Area, Padang - Firda Az zahra; Chairul Chairul; Indra Junaidi Zakaria (Bioscience, 2020)
The seagrass beds are the spawning, nursery, and the feeding ground for some oceanic biota. It’s also can trapped the sediment and stabilized the substrate so the waters looks clear. Beside those abilities, seagrasses are also can store the carbon. The research was conducted in karang tirta’s coastal area, padang city to analyze the carbon stock of seagrass that stored within their biomass. The biomass was analyzed by harvesting the seagrass at transect 25x25cm, while the carbon stock was analyzed by using walkley & black method. Seagrass beds in karang tirta’s coastal has 14,1 ha (142.546,36 m2) distribution area and it’s stored 18,05 tons of carbon. based on these result the seagrass beds in karang tirta’s coastal area has stored 1,2 tons C/ha. the highest carbon stock has found in the below ground, especially in their rhizomes.